Detritic Synovitis With Osteolysis Leading to Pathologic Fracture and Deltoid Avulsion Following Total Shoulder Arthroplasty. (November 2018) - Guild, Theodore; Onsen, Leonard T; Rivers, Marie; Cheski, Rebecca; Bear, Brian; Izquierdo, Rolando
Purpose: To report a unique case of detritic synovitis with associated lytic lesion leading to pathologic fracture of the acromion and deltoid avulsion following total shoulder arthroplasty (TSA). Methods: An institutional review board-approved retrospective case analysis was performed using Electronic Medical Records (EMR) sourced pathology and radiology results, clinic notes, and surgical reports. Case Description : We present the case of a 79-year-old woman with a surgical history significant for TSA who presented with new onset of shoulder pain. The patient was found to have a lytic lesion in the acromion secondary to an inflammatory reaction to polyethylene wear debris. The lytic lesion led to fracture of the acromion and avulsion of the deltoid muscle. The patient was treated with an open biopsy, culture, and repair of the deltoid avulsion. Discussion: This is a previously unreported complication of TSA resulting from detritic synovitis, a destructive inflammatory reaction to polyethylene wear debris within an artificial joint. The differential diagnosis includes periprosthetic infection with osteomyelitis and metastatic disease. This patient presented with extensive osteolysis, pathologic fracture of the acromion and deltoid avulsion that was successfully treated with debridement and surgical repair of the deltoid. Conclusion: As the prevalence of TSA rises, orthopedic surgeons should be aware of the possibility of detritic synovitis in patients who present with pain after shoulder arthroplasty with imaging studies demonstrating periarticular osteolysis.